Educar por competências: ressignificando o ensino religioso - Scussel, Marcos André (2013)
Is religious education through competences possible and what competences are necessary to be developed in this curricular component so as to contribute to the full formation of the student? This is the central question of this thesis. In the quest for answers we journeyed on the path of religious education and of education. The personal context and the spacetime of religious education were the starting points. The history of religious education in Brazil was revisited in its different phases and in the changes which the LDB 9.394/96 and the Law 9.475/97 brought to this component. We sought the interfaces between theology, religious sciences and religious education. The National Curricular Parameters for Religious Education and the guidelines and programs of eight states and five municipalities were available on the site of the GPER were analyzed to identify if they presented or were organized by competences. These elements contributed to the understanding of the spacetime of religious education which continues to seek affirmation. In a second moment we looked at the context of education. According to Brazilian legislation, the goals of education should be the full development of the human being, his/her holistic formation and formation for citizenship. Faced with the current context, teaching by competences presents itself as an answer to the challenges of contemporary education. The theme of competences was studied further, based on studies of Perrenoud, Zabala and Sacristán. The ENEM test National Examination of Secondary Education, was analyzed since it is a system which evaluates competences. Some of the elements of the religious phenomenon present in the 1,633 questions published in fourteen years of ENEM, from 1998-2011 were presented. Upon encountering religious knowledge in the evaluation of general competences of education, the possibility of developing a religious education centered on the development of competences was inferred. This reflection was developed in the third part of this thesis. The Curricular Matrix of Religious Education of the UMBRASIL was also analyzed. In a process of analysisauthorship, the journey of the construction, the partial results and the final redaction were shared. Based on this experience of this construction and of the competences evaluated with religious knowledge, the possibility of constructing a system of references for a matrix of competences for religious education was deduced. We concluded that religious education can and should contribute to the holistic formation of the human being and to the formation for citizenship. We followed up with the possibility of developing competences for religious education and of building a reference matrix. Based on the matrix of the ENEM: have dominion of languages; comprehend phenomena; confront problem situations; construct argumentations and elaborate proposals, five macro-competences were elaborated to be developed in religious education.